AB0005 Investigation of the Genetic Overlap Between Rheumatoid and Psoriatic Arthritis in a Genetic Homogeneous Population of Greece. (9th June 2015) - Myrthianou, E.; Zervou, M.I.; Kougas, N.; Terizaki, M.; Boumpas, D.T.; Kardassis, D.; Sidiropoulos, P.; Goulielmos, G.N.
Abstract : Background: Genome wide association studies (GWAS) have detected a big number of rheumatoid arthritis (RA) susceptibility genes (1) and, given the genetic overlap between various autoimmune diseases (2), some RA-associated genes were found also to be associated with psoriatic arthritis (PsA) (3). Objectives: We sought to investigate whether a single nucleotide polymorphism (SNP) of the PLCL2 (rs4535211), CCL21 (rs2812378), REL (rs13017599), STAT4 (rs10181656) and CD226 (rs763361) genes, previously reported as RA and/or PsA susceptibility loci in other populations (3), are associated with risk for these diseases in a genetic homogeneous Greek population. Methods: A group of 392 RA patients, 126 PsA patients and 521 healthy controls, age- and sex-matched, from the island of Crete, was included in this study. Genotyping of the SNPs under investigation was performed with Taqman primer-probe sets, by using a Real-Time PCR platform (Applied Biosystems, ViiA™ 7 Real-Time PCR System). Odds ratios (OR) and 95% confidence intervals (CI) were calculated and the statistical difference in allele distribution was assessed by means of x 2 test or Fisher's exact test. Results: Significant evidence for association with PsA was found for GG genotype and allele G of the rs10181656 SNP of STAT4 gene (p=0.04, OR=4.3, 95% CI 1.01-18.39 and p=0.03, OR=1.46, 95% CI 1.03-2.08, respectively). Association with PsA was also found for TT genotype of the rs763361 SNP of CD226 gene (p=0.04, OR=0.61, 95% CI 0.39-0.95), while no association of this SNP was found for RA. No association was found to the rest three loci examined. Bioinformatics analysis revealed that the C, but not the G, allele of the rs10181656 SNP of STAT4 is located within a putative binding site for transcription factors Pax-4, PPAR/RXR and ZNF99. Conclusions: In the current study, the genetic association of STAT4 rs10181656 and CD226 rs763361 SNPs with PsA only was confirmed in a Greek population, although the CD226 SNP was reported previously to confer a remarkable degree of risk for RA but not with PsA (4). Importantly, the PsA-associated allele of STAT4 SNP is protective and not risk, as presented elsewhere (3). The different findings of this study from previous ones highlight the importance of comparative studies that include different ethnic or racial populations in any attempt to confirm genetic associations detected. The putative role of the rs10181656 SNP in the regulation of the STAT4 gene via PPAR/RXR, a T-cell activator, is under investigation. References: Stahl EA, Raychaudhuri S, Remmers EF et al (2010). Nat Genet. 42(6):508. Gregersen PK, Olsson LM. (2009). Annu Rev Immunol 27:363. Bowes J., Ho P., Flynn E. et al. (2012). Ann Rheum Dis 71(8):1350. Hafler JP, Maier LM. et al. (2009). Genes Immun. 10(1):5. Disclosure of Interest: None declared